Investigation of the Influence of Changes in the Parameters of Venturi Tube Orifice Plates on the Cavitation Effect - LI Dawei; GU Shijie; HAN Guihua; YANG Xudong (Journal of Harbin University of Science and Technology)
In order to study the influence of the parameter changes of venturi tube orifice plate on the cavitation effect, the cavitation mechanism and simulation conditions were described by theoretical modeling. The inlet pressure and hole cross-sectional area were variable parameters for single-factor numerical simulation, and the gas volume fraction rate was the cavitation effect characterization. The research results show that the cavitation is concentrated at the diffusion section of the venturi tube and the cavitation effect of venturi tube orifice plate increases with the increase of inlet pressure; the vortex cavitation phenomenon gradually increases when the inlet pressure is greater than 1. 1 MPa; the hole cross-sectional area increases with the increase of venturi tube orifice plate cavitation effect. The cavitation effect of venturi tube orifice plate is enhanced by increasing the cross-sectional area, and the cavitation effect of multiple channels is improved under the same cross-sectional area. Finally, the experimental investigation of the variable parameters is conducted by conductivity cavitation water experiment, yielding the same conclusion as the numerical simulation, proving the reliability and accuracy of the numerical simulation.